Piezoresistive damage sensing and mechanical characteristics of carbon/glass hybrid thermoplastic composites. (May 2023) - Shonar, Mohammed; Chalivendra, Vijaya
A comprehensive experimental investigation is performed to understand the damage sensing capabilities of thermoplastic intra-ply carbon/glass laminated composites embedded with Carbon Nanotubes (CNTs) under quasi-static interlaminar shear and mode-I fracture loading conditions. CNTs are dispersed in thermoplastic Elium® resin using a combination of ultrasonication and shear mixing processes. This resin mix is used in a vacuum infusion process to fabricate four different intra-ply laminated composites orientations; G-0-C-90 [Carbon fibers are in the longitudinal direction], G-90-C-0 [Glass fibers are in the longitudinal direction], G-45-C-45(R) [carbon and glass fibers are at +45°, and −45° from the longitudinal direction and form a repeating layup], and G-45-C-45(A) [carbon and glass fibers are at +45°, and −45°, but with alternating directions for each lamina in the layup]. Four-circumferential probes are utilized to obtain the piezo-resistance measurements associated with damage inside the composites under shear and mode-I loadings. In the shear experimentation, the G-45-C-45(A) orientation demonstrated the largest interlaminar shear strength, at 50% greater than the G-45-C-45(R) orientation. Both G-45-C-45(A) and G-45-C-45(R) had significantly larger shear strains compared to the G-90-C-0 and G-0-C-90 orientations. However, the best resolution in shear damage sensing was seen with the G-0-C-90 composites. In the mode-I fracture experiments, the greatest fracture initiation toughness is shown with the G-0-C-90 orientation, which is 80% greater than the G-90-C-0 orientation. Compared to all orientations, the G-0-C-90 orientation also provided the most sensitive electrical response.